Frequency of gene sequences necessary for pyelonephritis-associated pili expression among isolates of Enterobacteriaceae from human extraintestinal infections. - Hull, R A (1984)
Bacteria representing eight genera of the Enterobacteriaceae were collected from human extraintestinal infections and examined to determine whether they contained gene sequences necessary for expression of a pili type often associated with bacteria causing human pyelonephritis. Escherichia coli isolated from most of the extraintestinal sites were frequently found to possess pap-related DNA sequences. Isolates which possessed these sequences were often found to exhibit D-mannose-resistant hemagglutination of human erythrocytes and to have surface antigens related to P pili.